Fecal contamination and antimicrobial susceptibility profiles of Escherichia coli in rural water sources of Bali, Indonesia - I WAYAN AGUS GEDE MANIK SAPUTRA; I PUTU BAYU MAYURA; MADE AGUS HENDRAYANA; I WAYAN SUARDANA; NI NYOMAN SRI BUDAYANTI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Saputra IWAGM, Mayura IPB, Hendrayana MA, Suardana IW, Budayanti NNS. 2025. Fecal contamination and antimicrobial susceptibility profiles of Escherichia coli in rural water sources of Bali, Indonesia. Biodiversitas 26: 4923-4931. Escherichia coli is a key indicator of human fecal contamination in environmental waters, providing insight into sanitary conditions and potential health risks, including the presence of diarrheagenic genotypes and antimicrobial-resistant strains such as extended-spectrum ?-lactamase (ESBL) producers. This study assessed fecal coliform contamination in rural water sources and characterized E. coli isolates for pathogenic potential and antimicrobial susceptibility within the context of the SAJAKA (Antibiotic-Wise Village) Project in Bali, Indonesia. A cross-sectional survey was conducted in August 2024 across 24 sites, including 16 river points (upstream, midstream, downstream) and 8 springs, in four rural villages. Single 250 mL water samples were analyzed using the Most Probable Number (MPN) method, cultured in Lactose Broth at 37°C, and confirmed in Brilliant Green Lactose Bile Broth at 44.5°C. Positive cultures were transferred to eosin methylene blue agar, colonies with a metallic green sheen were purified and identified using the VITEK 2 Compact system, and confirmed E. coli isolates were subjected to PCR to detect virulence-associated genes. Fecal coliforms were detected in 41.7% of sites (10 of 24, n=24) of sites, with higher prevalence in rivers (8 of 16, 50%) compared to springs (10 of 24, 25%), and spatial clustering was observed in downstream segments of the Yeh Ge and Yeh Dati Rivers. Eight isolates were identified as E. coli and two as Klebsiella pneumoniae subsp. pneumoniae. None of the E. coli isolates carried virulence genes of diarrheagenic pathotypes, and all were susceptible to third-generation cephalosporins, indicating the absence of ESBL production. Although ESBL and diarrheagenic E. coli were not detected, the presence of E. coli indicates contamination and therefore the water is nonpotable and calls for corrective action. Continued monitoring, particularly for antimicrobial resistance, is essential to support water safety and public health strategies within a One Health framework.